Aged garlic extract suppresses inflammation in apolipoprotein E‐knockout mice. Issue 10 (29th August 2017) - Morihara, Naoaki; Hino, Atsuko; Miki, Satomi; Takashima, Miyuki; Suzuki, Jun‐ichiro
Abstract : Scope: Chronic inflammation plays a major role in the formation and progression of atherosclerotic plaques. To clarify the mode of action of aged garlic extract (AGE) to retard atherosclerosis, we investigated whether AGE suppresses the inflammation in apolipoprotein E‐knockout (ApoE‐KO) mice. Methods and results: ApoE‐KO mice were fed standard diet with or without 3% AGE for 12 wk. AGE feeding inhibited the progression of atherosclerotic lesion by 27% and reduced the level of C‐reactive protein (CRP) and thromboxane B2 (TXB2 ), a marker of platelet activation, in serum by 39 and 33%, respectively, compared to ApoE‐KO mice without AGE treatment. AGE treatment also decreased the level of tumor necrosis factor alpha (TNF‐α), a major stimulus inducing CRP production, in the liver by 35%. AGE decreased the level of interleukin‐1 receptor‐associated kinase 4 (IRAK4) by 60% and almost doubled the level of phospho‐AMP‐activated protein kinase (p‐AMPK) in the liver. Conclusion: The anti‐atherosclerotic effect of AGE involves the suppression of inflammation by reducing the serum level of CRP and TXB2, and the protein level of TNF‐α and IRAK4, and increasing AMPK activity in liver. Abstract : CRP, an inflammatory marker, promotes the development of atherosclerosis by enhancing vascular smooth muscle cells proliferation, recruitment of monocytes/macrophages, and platelet activation. The anti‐atherosclerotic effect of aged garlic extract (AGE) involves the suppression of inflammation by reducing the serum level of CRP and the protein level of TNF‐α and IRAK4, and modulating p‐AMPK in liver.